2010
DOI: 10.1007/978-1-4419-6354-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortins and the Cholinergic Anti-Inflammatory Pathway

Abstract: Experimental evidence indicates that small concentrations of inflammatory molecules produced by damaged tissues activate afferent signals through ascending vagus nerve fibers, that act as the sensory arm of an "inflammatory reflex". The subsequent activation of vagal efferent fibers, which represent the motor arm of the inflammatory reflex, rapidly leads to acetylcholine release in organs of the reticuloendothelial system. Acetylcholine interacts with α7 subunit-containing nicotinic receptors in tissue macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 141 publications
4
39
0
Order By: Relevance
“…The subsequent activation of vagal efferent fibers, which represent the motor arm of the inflammatory reflex, rapidly leads to acetylcholine release in organs of the reticuloendothelial system, including the spleen, liver, and gastrointestinal tract. Here acetylcholine interacts with α7 subunitcontaining nicotinic receptors in tissue macrophages and other immune cells, which inhibits NF-kappaB nuclear translocation and rapidly inhibits the synthesis/release of tumor necrosis factor-α and other inflammatory cytokines by monocytes and macrophages [45][46][47][48]. Monocytes have alpha7 nicotinic acetylcholine receptors that inhibit the production of proinflamatory cytokines by suppression of IkB phosphorylation and nuclear factor-kB transcriptional activity [49].…”
Section: Acetylcholine (Nicotinic)mentioning
confidence: 99%
“…The subsequent activation of vagal efferent fibers, which represent the motor arm of the inflammatory reflex, rapidly leads to acetylcholine release in organs of the reticuloendothelial system, including the spleen, liver, and gastrointestinal tract. Here acetylcholine interacts with α7 subunitcontaining nicotinic receptors in tissue macrophages and other immune cells, which inhibits NF-kappaB nuclear translocation and rapidly inhibits the synthesis/release of tumor necrosis factor-α and other inflammatory cytokines by monocytes and macrophages [45][46][47][48]. Monocytes have alpha7 nicotinic acetylcholine receptors that inhibit the production of proinflamatory cytokines by suppression of IkB phosphorylation and nuclear factor-kB transcriptional activity [49].…”
Section: Acetylcholine (Nicotinic)mentioning
confidence: 99%
“…Orally administered ACTH exerts anti-inflammatory effects in mice via modulation of regulatory T (Treg) cells [Szabo et al 1989]. Both ACTH 1-39 and ACTH 1-24 activate anti-inflammatory signals by potentiating sympathetic/adrenergic pathways [Gothert, 1984;Brzoska et al 2008], which play a role in the efferent anti-inflammatory cholinergic pathway [Giuliani et al 2010]. Neurotrophic effects were suggested in spinal cord injury and protective effects in ischemic brain injury [Catania et al 2004;Gong, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Through an efferent vagal pathway, central melanocortins protected rats against myocardial ischemia/reperfusion injury, ischemic stroke, and hemorrhagic shock. 16,44 Further, research on acute inflammation in the mouse indicated that ␣-melanocyte-stimulating hormone can act solely within the brain to inhibit nuclear factor-B activation in peripheral tissues. 43,44 This latter effect appeared to be mediated by sympathetic signals that require a peripheral ␤ 2 adrenergic receptor.…”
Section: Critical Care Medicinementioning
confidence: 99%
“…17,18 Conversely, the short half-life of peptide molecules, including natural melanocortins, that are broken down readily in the body fluids, should not represent a limitation as several of the generated fragments are biologically active. 10 Finally, passage through the blood-brain barrier 10,12,44,45 and lack of receptor selectivity of melanocortins should not be problematic in short-term, acute treatments such as in hemorrhagic shock.…”
Section: Critical Care Medicinementioning
confidence: 99%
See 1 more Smart Citation